2016
DOI: 10.1002/anie.201601364
|View full text |Cite
|
Sign up to set email alerts
|

A Drug‐Free Tumor Therapy Strategy: Cancer‐Cell‐Targeting Calcification

Abstract: Herein, we propose a drug-free approach to cancer therapy that involves cancer cell targeting calcification (CCTC). Several types of cancer cells, such as HeLa cells, characterized by folate receptor (FR) overexpression, can selectively adsorb folate (FA) molecules and then concentrate Ca(2+) locally to induce specific cell calcification. The resultant calcium mineral encapsulates the cancer cells, inducing their death, and in vivo assessments confirm that CCTC treatment can efficiently inhibit tumor growth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 44 publications
0
71
0
1
Order By: Relevance
“…Meanwhile, scientists investigated a complete calcification‐based tumour therapy. In the calcification treatment, the nuclei of tumour cells become agglutinated and abnormal, indicating that the CaP mineral coat promotes cell death (Figure C,D). It should be noted that both folate and calcium are essential ingredients in human metabolism and exhibit drug‐free features, which is a primary advantage of CCTC.…”
Section: Biological Strategy For Organism Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, scientists investigated a complete calcification‐based tumour therapy. In the calcification treatment, the nuclei of tumour cells become agglutinated and abnormal, indicating that the CaP mineral coat promotes cell death (Figure C,D). It should be noted that both folate and calcium are essential ingredients in human metabolism and exhibit drug‐free features, which is a primary advantage of CCTC.…”
Section: Biological Strategy For Organism Modificationmentioning
confidence: 99%
“…D) Confocal laser scanning microscopy (CLSM) images of a tumour slice stained with Hoechst 33342. Reproduced with permission . Copyright 2016, Wiley‐VCH.…”
Section: Biological Strategy For Organism Modificationmentioning
confidence: 99%
“…For example, a report showed that folate‐induced calcium phosphate formation at the surface of HeLa cells (and cancerous cells in vivo) ruptured the integrity of cell membranes and induced cell death. [ 28 ] This in situ mineralization approach might be applied to microbial cells, which have tougher cell walls, for the formation of self‐repairing shells.…”
Section: Dynamic Shellsmentioning
confidence: 99%
“…In this approach, certain in situ macromolecular systems are introduced or formed in situ inside the cell or subcellular compartments to lead to cell death either by physical damage or by inhibition of the metabolic function. Self-assembly, aggregation, polymerization, and biomineralization inside the cancer cells are emerging examples that could tackle cancer cells efficiently [68]. In the drug-free approach, the anticancer activity turns on once the macromolecular system interacts with the targeted cancer cell component while being inactive in their molecular state, thus inducing fewer side effects both in vivo and in vitro.…”
Section: Mitochondria-targeted Drug-free Agentsmentioning
confidence: 99%